LABORATORY VERIFICATION OF SUBMICRON MAGNETITE PRODUCTION IN PSEUDOTACHYLYTES: RELEVANCE FOR PALEOINTENSITY STUDIES - Nakamura N.; Hirose T.; Borradaile G.J. (My University, 2002)
Pseudotachylytes generally possess stable remanent magnetizations but the processes by which pseudotachylytes are magnetized remain poorly understood. Magnetic hysteresis and scanning electron microscope studies reveal that experimental frictional melting of granites produces dispersed submicron inclusions of weakly interacting pseudo-single-domain (PSD) magnetite, in artificial pseudotachylyte. The magnetite inclusions are absent in the undeformed granite protolith and result from oxidation of Fe in melt-susceptible mafic minerals during the melt-quenched event. The pseudotachylytes acquired a stable thermal remanence in fine-grained PSD magnetites during the rapid cooling of the melt, implying that fine-grained magnetite has the potential for paleointensity determinations of contemporaneous magnetic fields with co-seismic faulting in granitoids.
Keywords: PSEUDOTACHYLITE; THERMOREMANENT MAGNETIZATION; MELTING INCLUSIONS; PSEUDO-SINGLE-DOMAINS